2018
DOI: 10.3390/su11010156
|View full text |Cite
|
Sign up to set email alerts
|

Education for Sustainable Development: Emerging Themes from Adopters of a Declaration

Abstract: Universities that sign the Talloires Declaration signify their commitment to education for sustainable development. This research explores whether the signification is a strategic desire to be seen to be doing the right thing, or a genuine commitment to enhancing sustainability and helping the environment. This semi-structured interview research involves communication with the sustainability managers in the majority of Talloires signified universities in Australia. Since Australia has a comparably high rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Although no studies have previously examined universities' codes of ethics in a SD perspective, the results presented in this study could be compared with the conclusions of other international similar works. On the one hand, this analysis is, for example, in-line with that studies that argue that an (a) SD is a well-defined concept within higher education [11,50], (b) the SDGs have a global dimension and their action implementation depends on the level of priority that different countries give to them [51], (c) there are currently no international guidelines and best practices on sustainability in universities [35] and (d) only a small number of universities are communicating their sustainability efforts [11]. On the other hand, it is important to highlight how in the universities' codes of ethics some SDGs are totally excluded from the ethical actions of universities.…”
Section: Discussionsupporting
confidence: 78%
“…Although no studies have previously examined universities' codes of ethics in a SD perspective, the results presented in this study could be compared with the conclusions of other international similar works. On the one hand, this analysis is, for example, in-line with that studies that argue that an (a) SD is a well-defined concept within higher education [11,50], (b) the SDGs have a global dimension and their action implementation depends on the level of priority that different countries give to them [51], (c) there are currently no international guidelines and best practices on sustainability in universities [35] and (d) only a small number of universities are communicating their sustainability efforts [11]. On the other hand, it is important to highlight how in the universities' codes of ethics some SDGs are totally excluded from the ethical actions of universities.…”
Section: Discussionsupporting
confidence: 78%
“…Zutshi, Creed, and Connely [9] argued that sustainability initiatives should occupy a strategic place in higher education institutions, while Alba-Hidalgo, del Alamo, and Gutierrez-Perez [84] recognized the mature experiences associated with environmental sustainability in connection with the main pillars of a university's activity: teaching, research, facilities, and services. In this sense, universities began collaborating and adopting external standards.…”
Section: Content Analysismentioning
confidence: 99%
“…In recent years, numerous studies [1][2][3][4][5][6][7][8][9][10] have shown that the interest in research concerning Education for Sustainable Development (ESD) has grown considerably. As it expands rapidly, this sector is becoming more visible and significant in a global world affected by serious environmental issues and by growing social, economic, and political inequality.…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have seen considerable development, arguably stimulated by the United Nations Decade of Education for Sustainable Development (2005Development ( -2014, in the interdisciplinary debate on the biunivocal links between education and sustainability (Jickling and Wals 2008;Reunamo and Pipere 2011;Sterling 2016;Zutshi et al 2019). "The number of publications, authors, and journals has increased, proving that ESD has gained momentum" (Grosseck et al 2019, p. 30), while experts and scholars have focused on two main priorities, namely "international efforts to bring this area of inquiry into the mainstream [and] the integration of education into sustainable development and of sustainable development into education" (ivi, p. 1).…”
Section: Esd Between Universalism and Place-based Educationmentioning
confidence: 99%